2021
DOI: 10.1186/s42523-021-00101-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sequentially fed high protein, hydrolyzed protein, and high fiber diets on the fecal microbiota of healthy dogs: a cross-over study

Abstract: Background Dietary content and environmental factors can shape the gut microbiota, and consequently, the way the gut microbiota metabolizes fats, carbohydrates, and proteins, affecting overall health of the host. We evaluated the impact of 3 diets (all meat [raw], high-insoluble fiber dry extruded diet and hydrolyzed protein dry extruded diet) on the gut microbiota of healthy dogs in a cross-over sequential study. Results We showed that diet can ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 67 publications
4
12
0
Order By: Relevance
“…The 16S rRNA gene sequencing did not show differences in fecal communities between dogs fed hydrolyzed or common protein source diet. Although no differences were observed for fecal bacterial phyla between groups, the relative abundance verified for the HCLP group is in accordance with a previous study by Martı ´nez-Lo ´pez et al [33], in which healthy adult dogs also fed a hydrolyzed chicken liver diet for 6 weeks showed Firmicutes (median of 55%), Fusobacteria (median of 17%) and Bacteroidetes (median of 16%) as the most abundant bacterial phyla. Similarly, Bresciani et al [34] did not find changes on fecal microbiota of healthy dogs after 60 days of an animal protein-free diet consumption.…”
Section: Plos Onesupporting
confidence: 91%
See 2 more Smart Citations
“…The 16S rRNA gene sequencing did not show differences in fecal communities between dogs fed hydrolyzed or common protein source diet. Although no differences were observed for fecal bacterial phyla between groups, the relative abundance verified for the HCLP group is in accordance with a previous study by Martı ´nez-Lo ´pez et al [33], in which healthy adult dogs also fed a hydrolyzed chicken liver diet for 6 weeks showed Firmicutes (median of 55%), Fusobacteria (median of 17%) and Bacteroidetes (median of 16%) as the most abundant bacterial phyla. Similarly, Bresciani et al [34] did not find changes on fecal microbiota of healthy dogs after 60 days of an animal protein-free diet consumption.…”
Section: Plos Onesupporting
confidence: 91%
“…Alpha diversity was not affected by dietary treatments, but PCoA plots based on Bray-Curtis and D_0.5 UniFrac distance metrics showed a clear separation between control group and HCLP group, which was also verified previously in dogs fed hydrolyzed and anallergenic diets [33,41].…”
Section: Plos Onesupporting
confidence: 84%
See 1 more Smart Citation
“…Highprotein diets have been demonstrated previously to alter intestinal microbiota, resulting in decreased fecal short-chain fatty acid production, increased fecal branched-chain fatty acids, and a higher fecal pH compared to cats and dogs fed a lower protein diet. 33 Because we did not evaluate the intestinal pH of dogs prior to transitioning to the diet intended for cats, nor did we evaluate the intestinal microbiota or metabolic products, we cannot establish a causal relationship between the higher protein diet and the increased intestinal pH in our study dogs.…”
Section: Discussionmentioning
confidence: 97%
“…Several taxa became detectable in response to diet, such as Lactobacillus ruminis, which was detected in 59% of LPHC-fed dogs [48]. In another study, the fecal microbiota of dogs fed a HPLC diet showed an increased abundance of Bacteroidetes in addition to an enrichment in the phylum Firmicutes [49].…”
Section: Dietary Proteinsmentioning
confidence: 94%